Visible-light-mediated, nitrogen-centered radical amination of tertiary alkyl halides under metal-free conditions to form α-tertiary amines. Issue 19 (26th April 2016) - Brueckner, Alexander C.; Hancock, Erin N.; Anders, Evan J.; Tierney, Matthew M.; Morgan, Heather R.; Scott, Kristina A.; Lamar, Angus A.
Abstract : A mild and operationally convenient amino-functionalization of a range of tertiary alkyl halides that involves a N, N -diiodosulfonamide reactive species has been developed. Abstract : A mild and operationally convenient amino-functionalization of a range of tertiary alkyl halides by reaction with iminoiodinanes (PhINNs) and I2 has been developed. According to the mechanistic experiments described within, the reaction is speculated to proceed through a light-promoted, N-centered radical pathway involving a N, N -diiodosulfonamide reactive species. This method of direct N-incorporation offers an attractive alternative to the production of α-tertiary amines, a synthetically challenging structural class found in a variety of bioactive molecules.